Kiss me, Catalina - Oliveras, Priscilla (Montlake, 2022)
"Ambitious San Antonio singer Catalina "Cat" Capuleta gets the chance of a lifetime when she joins superstar heartthrob and fellow mariachi Patricio Galán on his seven-week concert tour. Demanding and arrogant, Patricio challenges Cat on every level, as an artist and as a woman. But headstrong Cat is determined to be his match. No matter how seductive Patricio's baritone voice, Cat's eyes are only on the prize: success and making her familia proud. No woman gets under Patricio's skin like Cat. Her talent mesmerizes. Her passion is thrilling. And her drive, stemming from an old unhealed family wound, exposes a vulnerability he secretly recognizes in himself. When the duo hits the road, the sparks don't just fly--they detonate. Stage by stage, as each reckons with the past--and with each other's quick-fire personalities--they bring crowds to their feet, and Cat's long-held dreams come true. Will their road romance go up in flames? Or could making music together kindle the most rapturous love song of their lives?"--